Respostas
respondido por:
2
Substitui
2(-3)² -3p - 3 = 0
2*9 - 3p - 3 = 0
18 - 3 - 3p = 0
15 - 3p = 0
p = 5
:)
2(-3)² -3p - 3 = 0
2*9 - 3p - 3 = 0
18 - 3 - 3p = 0
15 - 3p = 0
p = 5
:)
respondido por:
2
2x² + px - 3 = 0
2(-3)² + p.(- 3) - 3 = 0
2.9 - 3p - 3 = 0
18 - 3 - 3p = 0
15 - 3p = 0
15 = 3p
3p = 15
p = 15/3
p = 5
R.: p = 5
2(-3)² + p.(- 3) - 3 = 0
2.9 - 3p - 3 = 0
18 - 3 - 3p = 0
15 - 3p = 0
15 = 3p
3p = 15
p = 15/3
p = 5
R.: p = 5
Perguntas similares
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás